Evidence of haab associations in the Madrid Codex. - Vail, Gabriel (Revista Española de Antropología Americana, 2000)
Recent studies suggest that almanacs oceurring in the prehispanie Madrid Codex may be concerned with the coinmensuration of two calendars, 11w 260-day tzolkín aud the 365-day haab, as a means of scheduling ceremonies relevant to both the Maya ritual cycle and the solar year. This interpretation directly contradicís tlie traditional view of codical almanaes as devices used solely Por divination within the 260-day calendar. Utilizing data from ethnohistoric sources, this paper establishes linkages between activities represented in the Madrid Codex and haah ceremonies described in the Colonial literature. It concludes with a model demonstraring 1mw a series of almanacs that picture the manufacture of dcity images were interrelated. Calendrical models such as these offer the opportunity to better understand how the codex was used on a day-to-day basis by Maya priests and daykeepers ir Postclassic times.